Ibn Jarir al-Tabari's approach on the semantics of the literal association (al-Mushtarak al-Lafzi) in the Qur'an : an analytical study - Almuways, Yasir Sulaiman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research aims to bridge the gap that currently exists between the science of Tafsir (Interpretation) and the science of Translation in relation to the Literal Association Phenomenon in the Qur'an by collecting and studying the ʼayat of the Literal Associations (al-Mushtarak al-Lafzi) and their semantics (meanings) based on the perspectives and methodological principles used by Ibn Jarir al-Tabari in his Tafsir, which have not yet been explored in the science of Tafsir, and extracting those perspectives and methodological principles for the process of translating the Literal Association (al-Mushtarak al-Lafzi) in the Qur'an which is where the research problems lie. This research results in a disciplined systematic study with a clear methodological framework which will be used in the science of Translation in place of the translations of the Qur'an that have been conducted based on multiple books of Tafsir that vary and differ in their perspectives on linguistic phenomena as well as with their general and specific methodological frameworks which surely result in some semantic clashes and contradictions. Therefore, this research takes the approaches of Ibn Jarir al-Tabari in order to achieve consistent results with the semantics of the literal association which will reflect on the accuracy of its translation when translated. The research encompasses the concept of the Literal Association Phenomenon in Arabic Linguistics, Qur'an, and English Linguistics. It also introduces the framework and the concept of al-Tarjiḥ (outweighing one opinion over another) and al-Ikhtiyar (his selection of opinions) from Ibn Jarir al-Tabari's perspective which will enable the students of knowledge of Tafsir and qualified translators to fully understand why and how the choices of certain semantics of some ʼayat are selected and outweighed by Ibn Jarir al-Tabari. Consequently, this research is based on the analytical and inductive research methodologies in which the qualitative approach is employed in order to conduct the process of this research in the best and most accurate way possible. This research concluded with a number of results: An extraction of forty-six methodological rules for the process of translating the Literal Association (al-Mushtarak al-Lafzi) in the Qur'ān, an identification and investigation of the Literal Association (al-Mushtarak al-Lafzi) from Ibn Jarir al-Tabari with their semantic and literal meanings, and a translation of all the ʼayat in which the Literal Association (al-Mushtarak al-Lafzi) occurs with an accurate translation that coincides with the methods, the approaches, and the perspectives of Ibn Jarir al-Tabari. As a result, this research will be a significant and effective contribution and qualitative addition to the field of Tafsir and translation which are both linked together to serve and enhance people's understanding towards al-Qur'an al-Karim. The researcher has reached a number of recommendations, the most important of which are: the need for determining the methodology or type of Tafsir or Mufassir followed in the translation, such as determining whether it is al-Tafsir al-Maʼthur or the Tafsir of Jarir al-Tabari and so forth, and the need for knowing the backgrounds of al-Mufassir linguistically and in terms of their approaches of Tafsir.